Marital Satisfaction and Depression among Married Adults in Dhaka City: Exploring the Role of Socio-demographic Factors (Bangladesh Journal of Psychology, 2025)
Marital satisfaction and depression are intertwined factors significantly affecting the mental well-being of married individuals. The present study was designed to investigate the association between marital satisfaction and depression among married individuals in Dhaka city, with a focus on the role of sociodemographic factors. Data were collected from 390 married adults (208 males, 182 females; age range 21–55 years, M = 34.25, SD= 5.08) in Dhaka city. The Bangla versions of the ENRICH Marital Satisfaction Scale and the Beck Depression Inventory-II were used to collect data. The results revealed a significant negative correlation between marital satisfaction and depression (r = –.530, p < .01), indicating that higher marital satisfaction was associated with lower levels of depression. Results of the t-test revealed that females reported significantly higher levels of depression than males, although there was no statistically significant difference in marital satisfaction by gender. Participants from joint families reported greater marital satisfaction than those from nuclear families. ANOVA results indicated significant differences in depression across occupational groups and marital satisfaction across socioeconomic groups. Multiple regression analysis identified marital satisfaction, gender, and family type as significant predictors of depression, with marital satisfaction emerging as the strongest predictor. The overall model explained approximately 32% of the variance in depression scores, R² = .318, F(5, 382) = 35.56, p < .001. These findings emphasize the importance of marital satisfaction in the psychological well-being of married individuals in urban Bangladesh.Bangladesh Journal of Psychology, Vol. 25, December 2025, pp. 16-29